Efficacy of urine screening and culture methods in childhood urinary tract infections and analysis of the causative pathogens - J., Kavitha; D., Anuradha; M. A., Aravind; J., Ganesh (International Journal of Contemporary Pediatrics, 2017)
Background: Urinary tract infection (UIT) is common in infants and children causing significant morbidity and long- term complications. In infants and young children symptoms and signs of UTI tend to be non-specific A presumptive diagnosis can be supported with a microscopic examination of a urine specimen. Definitive diagnosis requires a semi-quantitative culture of urine. There has been growing interest in developing efficient technology, that can rapidly and accurately diagnose UTIs and guide the clinician on antibiotic preference for maximum therapeutic benefit. Methods: This prospective hospital-based study was conducted in patients from 2-12 years in a tertiary care hospital. Screening and confirmation of urinary tract infections by urine microscopy and urine culture and comparison, with an analysis of the bacterial strains and antibiotic sensitivity patterns was also done. Results: Among the 214 culture positive patients analysed in the study 64 were 2-5years of age and 150 belonged to 5 -12 years. 128 (59.5%) were boys and 86 (40.2%) were girls. Proteinuria was observed in 68 children (31.8%). Significant pus cells of >5/hpf was present in 77 (36%). E. coli was the commonest organism in 98 children (45.8%) with 100% of organisms were sensitive to amikacin. Conclusions: Over the years, the causative organisms of UTI in India have remained fairly constant but drug sensitivity has changed according to antibiotic usage. In the present era, the emergence of resistant strains poses a significant threat that can be ameliorated by rational and judicious antibiotic use.